The Persuasiveness of Assertives and Arguments in Ancient Stoicism - Dinucci, Aldo; Rudolph, Kelli (Revista Archai, 2022)
In the first part, we survey the occurrences of pithanon (‘persuasive’) and related terms in texts and fragments of Ancient Stoicism referring to the persuasiveness of assertibles and arguments, and fragments in which the Stoic logic is presented as the tool to avoid the persuasiveness of sophisms and the Stoic sage as the one who can efface this persuasiveness by his expertise in dialectics. Once it is done, we consider critically the assessments of Chiaradona Sedley and Tieleman, for whom Chrysippus is interested in extralogical forms of discourse, and also another thesis from Tieleman, according to which Chrysippus uses persuasive premises for constructive purposes. In our conclusions, we discard the thesis concerning Chrysippus’ recognition of extra-logical truths, on the basis of the Stoic ideal of the sage. We conclude that, in Stoicism, (1) pithanon refers primarily to false assertibles, arguments and presentations and (2) the Stoic sage cannot be persuaded, but he can persuade his students in order to prepare their souls to receive the Stoic doctrines.